PAH metabolites, GST and EROD in European eel (Anguilla anguilla) as possible indicators for eel habitat quality in German rivers - Kammann, Ulrike; Brinkmann, Markus; Freese, Marko; Pohlmann, Jan-Dag; Stoffels, Sandra; Hollert, Henner; Hanel, Reinhold (Environmental Science and Pollution Research, 2014)
The stock of the European eel (Anguilla anguilla L.) continues to decline and has reached a new minimum in 2011. Poor health status of the spawners due to organic contaminants is one of the possible causes for this dramatic situation. Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous contaminants, which are rapidly metabolized in vertebrates. EROD (ethoxyresorufin-O-deethylase) and GST (glutathione-S-transferase) are two enzymes involved in PAH detoxification in fish. In this study, PAH metabolites as well as EROD and GST activity in a large, comprising dataset of more than 260 migratory and pre-migratory eels from five large German river basin districts were used to describe PAH exposure and its metabolism as possible indicators for the habitat quality for eels. Eel from the river Elbe appear to be moderately contaminated with PAH. Highest mean values of PAH metabolites were analysed in fish from the river Rhine. However, the results suggest that contaminants such as PAH are metabolized in the fish and may have contributed to EROD activity in eels caught from the Elbe estuary to 600 km upstream. Since the eel’s onset of cessation of feeding is closely linked to maturation and migration, we propose bile pigments as new indicators contributing to identify the proportion of migratory eel, which is crucial information for eel management plans. We showed that PAH metabolites normalized to bile pigments as well as EROD could be used to describe the habitat quality and might be suitable parameters in search for suitable stocking habitats.